Estimation of yield and ultimate stress using the small punch test method applied to non-standard specimens: A computational study validated by experiments. (January 2018) - Priel, E.; Mittelman, B.; Haroush, S.; Turgeman, A.; Shneck, R.; Gelbstein, Y.
Highlights: Yield and UTS of thin specimens cannot be determined using classical SPT analysis. A computational study of non-standard SPT including specimen failure is provided. A novel method is proposed for evaluating Yield and UTS from non-standard SPT. Correction functions that account for different SPT setup parameters are provided. A good estimation was obtained compared to experiments using the proposed method. Abstract: In the last few decades there is a continuous demand for characterization of mechanical properties of metals and alloys using small specimens. This is especially true in the nuclear industry due to the limited number of irradiated standard specimens and strict safety regulations. One common method for small specimen testing is the Small Punch Test (SPT) method. In a previous publication by the authors, it was demonstrated that the accuracy in estimation of material yield and ultimate stress from classical analysis of SPT experiments deteriorates as specimen thickness decreases below t 0  = 300 µm. As a result, the classical equations for analysis of the SPT need to be corrected to be applicable to non-standard thin specimens. In the current study the finite element method incorporating a ductile damage model was used to investigate the SPT method applied to two very different representative materials with thickness values in the range of t 0  = 100 − 500 µm. The effect of SPT system setup on the load displacement curves was also examined. The thorough theoretical study enabled the formulation of novel correction functions for yield stress estimation which are independent of the material stress-strain response. An additional correction function for estimation of the ultimate stress based on strain energy and specimen thickness is also proposed. The proposed correction functions were validated using Tensile and SPT experiments on t 0  = 100,  200 µm thick SS316 L (Stainless Steel, grade 316 L). It is demonstrated that by applying the novel correction functions, a very good estimation of the yield and ultimate stress can be obtained from analysis of the SPT experiments. Graphical abstract: Image, graphical abstract Determination of yield stress from SPT experiments conducted on non-standard thin metallic foils and validation of the computational models by comparing computed and measured deformation and plastic strain.